2019
DOI: 10.1039/c9cy00555b
|View full text |Cite
|
Sign up to set email alerts
|

Structure-retentive synthesis of a highly ordered mesoporous Nb2O5/N-doped graphene nanocomposite with superior interfacial contacts and improved visible-light photocatalysis

Abstract: A highly ordered mesoporous Nb2O5/N-doped graphene nanocomposite was constructed for efficient photocatalytic H2 evolution under irradiation of visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…Owing to its flexibility in morphological, electronic, and structural properties, Nb2O5 is a promising candidate to design an effective heterojunction. Huang and coauthors reported a synergic combination of highly ordered mesoporous Nb2O5 (MNb) nanostructure to two-dimensional N-doped graphene (NGR) through a good interfacial connection ( Figure 3) [28]. UV/visible diffuse reflectance spectroscopy evidenced gradual shifts to longer wavelengths as the NGR quantity was increased, so the band gap energies were shift from 3.12 eV up to 2.67 eV.…”
Section: Niobium Pentoxide (Nb 2 O 5 )mentioning
confidence: 99%
“…Owing to its flexibility in morphological, electronic, and structural properties, Nb2O5 is a promising candidate to design an effective heterojunction. Huang and coauthors reported a synergic combination of highly ordered mesoporous Nb2O5 (MNb) nanostructure to two-dimensional N-doped graphene (NGR) through a good interfacial connection ( Figure 3) [28]. UV/visible diffuse reflectance spectroscopy evidenced gradual shifts to longer wavelengths as the NGR quantity was increased, so the band gap energies were shift from 3.12 eV up to 2.67 eV.…”
Section: Niobium Pentoxide (Nb 2 O 5 )mentioning
confidence: 99%
“…The Nb 3d spectrum (Fig. 4 d) exhibited two significant peaks at around 207.43 and 210.13 eV, corresponding to 3d 5/2 and 3d 3/2 states of Nb 5+ , respectively 60 . The O 1s XPS spectrum (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…1,2 Among a variety of semiconductor photocatalysts, niobium pentoxide (Nb 2 O 5 ) as an n-type photocatalyst displays a lot of unique physicochemical properties, including excellent chemical and thermal stability, and relatively high photocatalytic activity, making it a suitable photocatalyst for photodegradation. 3,4 However, Nb 2 O 5 can only be activated under UVlight irradiation because of its large band gap of $3.1 eV, making its use of solar energy less effective. 5,6 Additionally, the efficiency of a photocatalytic reaction is limited by a high recombination rate of photo-induced electron-hole pairs formed in the photocatalytic processes.…”
Section: Introductionmentioning
confidence: 99%